Determinants of director compensation in two-tier systems: evidence from German panel data - Jörn Michael Andreas; Marc Steffen Rapp; Michael Wolff (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2010)
Building on a unique panel data set of German Prime Standard companies for the period 2005-2008, this paper investigates the influencing factors of both director compensation levels and structure, i.e. the probability of performance-based compensation. Drawing on agency theory arguments and previous literature, we analyze a comprehensive group of determinants, including detailed corporate performance, ownership and board characteristics. While controlling for unobserved heterogeneity, we find director compensation to be set in ways consistent with optimal contracting theory. I.e. compensation is systematically structured to mitigate agency conflicts and to encourage effective monitoring. Thus, our results indicate that similar types of agency conflicts exist in the German two-tier setting.
Keywords: J33; G30; G34; 330; Director Compensation; Corporate Governance; Outside Directors; Two-tier System; Agency Costs; Führungskräfte; Vergütungssystem; Corporate Governance; Vertragstheorie; Prinzipal-Agent-Theorie